Análisis e interpretación de los estados financieros de la cooperativa de ahorro Y Crédito Cristo Rey de la ciudad de Loja, período 2011-2012 - Ochoa Soto, María Gabriela (2016)
This research work was carried out in order to analyze and interpret the financial statements of the credit union "Cristo Rey", in the period 2011-2012, through the application of techniques and procedures such as vertical analysis, horizontal and the application of financial indices which show the structure and financial activity of the Cooperative. Its content presents the Introduction, which highlights the importance of the subject under investigation, the theoretical framework contains the theoretical background in which the research is based development. The vertical and horizontal analysis of financial statements in the period 2011-2012 is developed to determine the current state of the union, ending with detailed credit portfolio analysis and financial structure. With regard to financial indicators, it develops a theoretical preamble, and then apply, interpret and compare with the values found at national cooperative system for these indicators. Finally, the conclusions that have been reached after the implementation of financial diagnosis and based on these recommendations could be implemented to improve the points that are considered to have shown a deficiency occurs.